2016
DOI: 10.4238/gmr15049016
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular enzymatic profiles and taxonomic identification of endophytic fungi isolated from four plant species

Abstract: Plants of medicinal and economic importance have been studied to investigate the presence of enzyme-producing endophytic fungi. The characterization of isolates with distinct enzyme production potential may identify suitable alternatives for specialized industry. At Universidade Estadual de Maringá Laboratory of Microbial Biotechnology, approximately 500 isolates of endophytic fungi have been studied over the last decade from various host plants, including medicinally and economically important species, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…This is the first report of hydrocarbon biodegradation by a fungus from the genus Saccharicola (97% ID). However, the production of extracellular protease enzymes has been confirmed in individuals of the genus [63], additional studies have identified fungal proteases due to their hydrolytic activity could participate in hydrocarbon degradation processes [57] [58].…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report of hydrocarbon biodegradation by a fungus from the genus Saccharicola (97% ID). However, the production of extracellular protease enzymes has been confirmed in individuals of the genus [63], additional studies have identified fungal proteases due to their hydrolytic activity could participate in hydrocarbon degradation processes [57] [58].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro cellulase and amylase activity was analyzed for 43 strains belonging to some of the most abundant taxa. The production of cellulase was assayed using the method described by Sunitha et al (2013) adapted to PDA plates. For each fungal strain a 6 mm diameter mycelial disk was placed in the center of a 9 cm.…”
Section: Methodsmentioning
confidence: 99%
“…In the current study, more than 85% of the isolates produced all these three enzymes which is in agreement with the previous reports of endophytic fungi from two mangrove species (Raviraja, 2005). Notable enzyme production (amylase, lipase and protease) could be observed for endophytic fungal species from medicinal plants also (Alberto 2016, Toghueo, 2017.…”
Section: Enzymatic Activitymentioning
confidence: 99%
“…It can be used in several areas, including food processing, leather industry, detergents, pharmaceuticals and medical therapy (Alberto, 2016;Lobo, 2005;Martinho, 2019).…”
Section: Introductionmentioning
confidence: 99%